Governance and public health expenditure in Côte d'Ivoire: examination of the dynamic relationship - Alliou Salihini Diarrassouba; Foungnigué Noé Coulibaly; Anzoumana Comoé (Health Economics Review)
Abstract Background The difficulties in mobilizing financial resources in developing countries combined with the low level of health of populations reveal the need to seek levers for optimal use of available resources. This paper aims at analyzing the dynamics of the relationship between governance and public health expenditure in Côte d’Ivoire as part of the “health for all” policy. Methods The estimates show, from a cointegration model based on the ARDL (self-regressive with staggered delays) approach and causality in the sense of that corruption influences and causes the increase in public health expenditure in the long term. Results The results includes poor health outcomes due to the diversion of resources on budgetary allocations. A 1% increase in the level of corruption generates 0.9% short-term and 0.5% long-term decrease in public health spending. Also, causality indicates a unidirectional link between the two variables ranging from corruption to the level of public health resources. Conclusions The authorities should therefore strengthen the institutional framework and the quality of central and internal governance of vertical health structures and programs in order to induce better use of resources likely to improve health outcomes.